Optimal Design of Bank Bailouts: Prompt Corrective Action - J-P. Niinimaki (Aboa Centre for Economics (ACE), 2011)
The paper investigates the optimal design of bank bailouts. Under three types of ex post moral hazard that tempt banks to hide loan losses, the paper analyzes banking regulation via three Prompt Corrective Action instruments: prohibition of dividends, limits on compensation to managers and early closure policy. The first two have a mitigating effort on moral hazard but the last instrument has a damaging impact. As to bad debts and the cleaning of banks' balance sheets, asset insurance and equity capital motivate banks to disclose loan losses. In some cases, prohibition of dividends or limits on compensation to managers has the same effect.
Keywords: G21; G28; 330; Financial intermediation; Mechanism design; Bank bailouts; Banking regulation; Prompt Corrective Action